2018
DOI: 10.3139/120.111178
|View full text |Cite
|
Sign up to set email alerts
|

Effects of process parameters on the quality of PLA products fabricated by fused deposition modeling (FDM): surface roughness and tensile strength

Abstract: This study investigates the effects of process parameters on the quality of products fabricated by fused deposition modeling (FDM), such as surface roughness and tensile strength. Polylactic acid (PLA) samples were built on a FDM machine at various layer thicknesses, nozzle temperature and deposition head velocity. The effect of cooling the samples during the process was also considered. The experimental study was performed according to a mixed type Taguchi L16 orthogonal array. The effectiveness of each param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 19 publications
1
39
0
1
Order By: Relevance
“…For instance, Altan et al [14] studied the effect of process parameters on surface roughness and the tensile strength on polylactic acid (PLA) samples. The samples were fabricated as per the ASTM standards and a Taguchi L16 experimental design, using three parameters: layer thickness, deposition head velocity, and nozzle temperature.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Altan et al [14] studied the effect of process parameters on surface roughness and the tensile strength on polylactic acid (PLA) samples. The samples were fabricated as per the ASTM standards and a Taguchi L16 experimental design, using three parameters: layer thickness, deposition head velocity, and nozzle temperature.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the surface roughness for PLA material ranged between 2.46 µm and 22.48 µm. In another research [13], there was used layer thickness between 0.1 mm and 0.4 mm to create PLA samples using a FDM process. The measured surface roughness fluctuated around 10 µm.…”
Section: Introductionmentioning
confidence: 99%
“…It is also evident from the searches that most of the authors are mostly focused on one-sided experiments. For example, the influence of process parameters on surface roughness [4,11,13], on dimensional or geometrical accuracy [14][15][16][17] is investigated, or mechanical properties and topography of printed samples are investigated [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Poor surface quality of the ME-made PLA parts that contains the deleterious staircase structure constrains their application as a final product for medical applications. Other than improving the surface quality by optimizing the processing parameters [23,24], post surface treatment reduces the deleterious staircase surface characteristics of ME products, which can be directly quantified by a reduction of surface roughness. Studies have investigated different post processing methods for improving surface quality of the ME products [25,26], such as barrel finishing, vapour smoothing and chemical etching techniques [27,28].…”
Section: Introductionmentioning
confidence: 99%